IMPACT OF REACTION TIME ON 50M FREESTYLE PERFORMANCE IN MALE SWIMMERS: A DIFFERENTIAL ANALYSIS ACROSS QUALIFICATION LEVELS - Zaitsev V.S. (Theory and Practice of Physical Culture, 2025)
Objective of the study. This study investigated the relationship between start reaction time (RT) and 50-meter swimming race performance across different swimmer qualification levels. The precise nature and strength of this relationship may vary significantly depending on an athlete’s skill proficiency. A large dataset comprising 2,252 competitive swimmers was analyzed and categorized into Elite (n=471), High-Level (n=574), and Medium-Level (n=1207) groups based on their competitive results. The overall analysis of the combined sample revealed a statistically significant positive correlation between RT and 50-meter race time (r=0.5078, p<0.0001), with RT explaining 25.78% of the variance in swimming performance. However, a differential analysis by qualification level demonstrated notable variations. For Elite swimmers, the correlation was r=0.2083 (p<0.0001, R2=4.34%), indicating a weak but significant association. High-Level swimmers showed the weakest correlation (r=0.1043, p=0.0124, R2=1.09%). Medium-Level swimmers exhibited the strongest group-specific correlation (r=0.2404, p<0.0001, R2=5.78%). While RT is a statistically significant factor influencing overall swimming performance, its predictive power substantially diminishes within more homogenous, higher-qualified groups. The results highlight the general importance of start efficiency in competitive swimming but also underscore the increasing dominance of other performance determinants (e.g., technique, power, endurance) as skill level advances. This differential impact provides valuable insights for targeted coaching strategies, suggesting a varied emphasis on start training based on a swimmer’s current qualification level.